Mathematical modelling of variable focus zoom imaging system with system identification technique, position control of lenses, and application to the produced system - Genc, Ebru; Polat, Mehmet (Springer Heidelberg, 2022)
Optical, electro-optic, and opto-mechanical components are used to visualize the targets. Variable-focus (zoom) optical imaging systems are used for the vision of the target in different ranges clearly. These systems which are also known as the zoom systems need to move linearly in some of the lens groups in the objective. This movement can be provided manually or by the help of the motor. Optical and mechanical design are difficult since these systems contain moving lens groups and require precise position control. In this paper, by giving general information about variable focus imaging systems, the most appropriate mechanism that constitutes the decided system and the mathematical model of the system which has been designed and extracted. In the derived mathematical model, the system identification method is used by considering the nonlinear structure and complexity of the system. Some studies on the position control of the optical system are realized by using MATLAB/Simulink simulation and also a prototype system is produced. It is observed that the results of the position control obtained from the prototype system capture the given reference inputs with great accuracy. Thus, the success of the system identification method which is used to derive the mathematical model of the optical system has been demonstrated both in the simulation and the experimental works.